Can Heparin-Coated ECMO Cannulas Induce Thrombocytopenia in COVID-19 Patients?. (7th June 2021) - Steinlechner, Barbara; Kargl, Gabriele; Schlömmer, Christine; Holaubek, Caroline; Scheriau, Georg; Eichinger, Sabine; Gratz, Johannes; Rössler, Bernhard
Abstract : Extracorporeal membrane oxygenation (ECMO) is often used in the management of COVID-19-related severe respiratory failure. We report the first case of a patient with COVID-19-related ARDS on ECMO support who developed symptoms of heparin-induced thrombocytopenia (HIT) in the absence of heparin therapy. A low platelet count of 61 G/L was accompanied by the presence of circulating HIT antibodies 12 days after ECMO initiation. Replacement of the ECMO system including cannulas resulted in the normalization of the platelet count. However, the clinical situation did not improve, and the patient died 9 days later. Careful consideration of anticoagulant therapy and ECMO circuit, as well as routine HIT antibody testing, may prevent a fatal course in ECMO-supported COVID-19 patients.